2019
DOI: 10.1177/1557988318823904
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Psychiatric Morbidity and Course of Distress in Males Undergoing Infertility Evaluation Is Affected by Their Factor of Infertility

Abstract: This panel study aimed to explore the effects of male, female, mixed or idiopathic factor of infertility on the course of clinical distress and possible psychiatric morbidity in involuntarily childless males undergoing fertility evaluation for the first time. A sample of 255 males completed the General Health Questionnaire-28 (GHQ-28) (a) at the baseline, before their initial fertility evaluation (T 1 ); (b) before their second andrological appointment 2–3 months after diagnostic disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Specifically, in women, couple's adjustment was also predicted by anxiety attachment, while in men other predictors of couple's adjustment were helplessness and type of diagnosis. In particular, husbands who had a mixed or idiopathic infertility factor reported lower levels of marital adjustment compared with other men, confirming results of other studies which underlined the role of diagnosis type in moderating the impact of infertility on individual and interpersonal well-being (Winkelman et al, 2016;Warchol-Biedermann, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Specifically, in women, couple's adjustment was also predicted by anxiety attachment, while in men other predictors of couple's adjustment were helplessness and type of diagnosis. In particular, husbands who had a mixed or idiopathic infertility factor reported lower levels of marital adjustment compared with other men, confirming results of other studies which underlined the role of diagnosis type in moderating the impact of infertility on individual and interpersonal well-being (Winkelman et al, 2016;Warchol-Biedermann, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…And again, unexplained infertility was found to be associated with the highest sexual impact ( Winkelman et al, 2016 ). A similar result was reported by Warchol-Biedermann (2019) , who found that participants with a mixed or idiopathic factor of infertility reported higher levels of distress.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The risk of depression can be determined by the male’s age, income, cause of infertility, prognosis, duration of infertility, availability of affordable treatments, and perceived social support. The physical and psychological burdens of obtaining the diagnosis and the treatment of unintended childlessness may affect the quality of life of males from couples with an unfulfilled child wish ( Bechoua et al, 2016 ; Gameiro et al, 2012 ; Hanna & Gough, 2015; Holter et al, 2007 ; Kumbak et al, 2010 ; Martins et al, 2016 ; Pook & Krause, 2005 ; Schmidt et al, 2012 ; Warchol-Biedermann, 2019 ; Wischmann et al, 2009 ; Wischmann & Thorn, 2013 ). The term quality of life, defined as one’s perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards, and concerns, remains an important issue in reproductive medicine and has often been used in the analyses of psychological outcomes of unwanted childlessness ( The WHOQOL Group, 1998 ).…”
mentioning
confidence: 99%
“…Attention to psychological and emotional needs is very essential especially in Iranian infertile couples because prevalence of depression in these couples was high [ 25 ]. Besides, previous studies showed that men's depressive symptoms increase in male factor infertility and more attention to their emotional counseling is necessary [ 26 , 27 ]. Although the cause of infertility in half of participants in the current research was different from the cited studies, their remarks showed that establishing counseling center can meet their various needs.…”
Section: Main Textmentioning
confidence: 99%